Towards real-time sign language analysis via markerless gesture tracking - Akmeliawati, Rini; Dadgostar, Farhad; Demidenko, S.; Gamage, N.; Kuang, Y.C.; Messom, C.; Ooi, M.; Sarrafzadeh, A.; SenGupta, G. (2009)
This paper introduces the gesture and hand posture tracking systems for a prototype real-time New Zealand sign language recognition system. The novelty of this work is in the markerless tracking of 13 gestures plus an unknown gesture category. Currently the gesture set is limited, but over time a more extensive gesture library can be developed and trained using the same technique. The hand posture system currently uses markers to obtain the high level of accuracy required for recognition of spelling of words in sign language using finger-pointing. Markerless hand posture detection has been shown to be more challenging especially with different signers who have not been used to train the system.